STUDI KASUS: PENGARUH PENERAPAN POSISI PRONASI DAN FISIOTERAPI DADA DALAM ASUHAN KEPERAWATAN ANAK DENGAN PNEUMONIA - Alya Pazirah; Regina Natalia (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
Pneumonia is an acute infection that attacks lung tissue (alveoli) caused by bacteria, viruses, and fungi. Pneumonia occurs when germs defeat the immune system, causing inflammation of the lungs and causing the air sacs in the lungs to become inflamed and swollen. In 2020, pneumonia was still the second leading cause of death in toddlers in Indonesia. The purpose of this paper is to determine nursing care for children with pneumonia by applying the prone position and chest physiotherapy to maintain airway clearance in hospitalized children. The method used is a case study (single case study) which is carried out based on the stages of nursing care including assessment, diagnosis, intervention, implementation, and evaluation of nursing. The results of the study showed that the data found in children were that the child appeared short of breath, chest wall retraction (intracosta), thick white sputum, and there were additional breath sounds (ronchi). The nursing problem in children is that airway clearance is ineffective, so the planned intervention is airway management with actions taken including applying the prone position and chest physiotherapy which showed that the problem was resolved. From this study, it can be concluded that the prone position and chest physiotherapy can improve airway clearance in children with pneumonia. Furthermore, it is expected that these actions can be implemented in the health service setting by nurses.